Book Review – Ibn Taymiyyah on Jihád and Baghy - Mohd Sharif, Mohd Farid (Penerbit Universiti Sains Malaysia (USM Press), 2012)
This book provides a scholarly examination of two highly controversial and widely misunderstood concepts in the contemporary world: jihād and baghy (rebellion). It approaches this topic from the perspective of one of the most influential figures of classical Islamic thought, Ibn Taymiyyah, the 7–8th (AH)/13–14th (CE) scholar. Ibn Taymiyyah, a revivalist teacher and jihadist of his own day, continues to have an impact on Islamic movements of today. The author helps us to view this medieval jurist's ideas beyond the polemical discourses of our times, while noting important themes in his thought that hold special significance for our volatile world. From the outset, Mohd Farid dispenses with the false notions that jihād is solely military or non-military, instead showing us how classical scholars, including Ibn Taymiyyah, viewed jihād as a combination of both. Similarly, many are often mistaken about what constitutes baghy and how we should understand its status and those who perform it. This book helps to clarify these crucial matters making it an essential contribution to existing literature on medieval Islamic thought. Moreover, given the way this book situates Ibn Taymiyyah within his historical context and discusses pertinent issues in our times, it is not only an important source for religious studies but also for the sociology and anthropology of knowledge.